2022
DOI: 10.1007/s00520-022-07319-5
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care interventions for cancer patients in low- and middle-income countries (LMICs): a scoping review

Abstract: In high-income countries (HICs), supportive care is often implemented to assist cancer patients as they seek treatment and beyond. However, in low-and middle-income countries (LMICs), where more than 70% of all cancer-related deaths occur [1], the provision of supportive care has not been assessed. The purpose of this scoping review is to assess the type of supportive care interventions for cancer patients that are being implemented into practice across the cancer care continuum in LMICs. MethodsWe examined pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The urgency of increased funding for such research in LMICs, as well as the promotion and dissemination of best practices, was also raised. 3 …”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The urgency of increased funding for such research in LMICs, as well as the promotion and dissemination of best practices, was also raised. 3 …”
Section: Main Textmentioning
confidence: 99%
“…This notion is corroborated by a scoping review of supportive care interventions for cancer in LMICs, which revealed a complete absence of interventions addressing the social and practical challenges stemming from cancer diagnoses, including financial toxicity, employment disruption, disability, and stigma. 3 …”
Section: Introductionmentioning
confidence: 99%
“…(5) What has or has not changed regarding your experience from the time of your diagnosis? (6) What changes do you want to see happen to your plan of care?…”
Section: Data Collectionmentioning
confidence: 99%
“…Many cancer programs in sub-Saharan Africa prioritize curative interventions that fail to address patients' sociocultural, psychological, spiritual, and physical palliative needs, missing critical opportunities to improve quality of life and alleviate suffering, 6,7 often complicated by humanitarian crises and armed conflict 8-10 . Liberia is a postconflict, low-income West African nation with an estimated 5000 health workers providing care for a population of approximately 5 million people (Table 1).…”
mentioning
confidence: 99%
“…Consequently, it is essential for cancer survivors to understand their diagnosis, treatment plan, and follow-up procedures, while also receiving the necessary physical and emotional support for effective cancer treatment. [12,13].…”
Section: Introductionmentioning
confidence: 99%